Pengaruh Peran Kepala Sekolah, Budaya Sekolah dan Motivasi Kerja terhadap Pengembangan Keprofesian Berkelanjutan Guru Sekolah Dasar di Kecamatan Ambarawa Kabupaten Semarang - Widiyanengsih, Widiyanengsih; Sudana, I Made; Murniati, Ngurah Ayu Nyoman (PGRI Kota Semarang, 2024)
This study aims to determine: (1) the influence of the principal's role on sustainable professional development; (2) the influence of school culture on sustainable professional development; (3) the influence of work motivation on sustainable professional development; (4) the influence of the principal's role, school culture, and work motivation on sustainable professional development. This type of research is quantitative research. The population in this study were elementary school teachers in Ambarawa District, namely 21 elementary schools. The number of samples was 133 children. The data collection method was in accordance with quantitative principles and aimed to test the proposed hypothesis. The purpose of ex-postfacto research is to test the hypothesis or answer questions related to the real conditions of the subjects studied. The results of the study showed that: There is a significant influence of the Principal's Role, School Culture, and Work Motivation on the Sustainable Professional Development of elementary school teachers in Ambarawa District, Semarang Regency, with a sig. value of 0.000 <0.05.